2011
DOI: 10.3795/ksme-a.2011.35.11.1521
|View full text |Cite
|
Sign up to set email alerts
|

Material Properties for Reliability Improvement in the FEA Results for Rubber Parts

Abstract: We studied the material properties for reliability improvement in finite element analysis results for a nitrile butadiene rubber hub-bearing seal and for a carbon-filled rubber mount used in a vehicle. It was difficult to measure the material properties of hundreds of types of rubber for the mount design. Thus, we suggested that the engineering stressstrain relations from pure shear test data could be synthesized by using simple tension data and Poisson's ratio. We defined Poisson's ratio by using a function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
0
0
1
Order By: Relevance
“…It is confirmed that the sealing capability of both types is fairly good, but the wrinkle type is better than the pot type in terms of the maximum stress. (8,9) 이러한 고 무의 특성을 잘 묘사하기 위해 고무의 인장시험 을 수행하였으며 그 결과로부터 과 같이 Table 1 함수 Ogden (9,10) 를 이용한 고무의 물성치를 구하 여 해석을 수행하였다. (7) 의 기능을 이용하여 단계의 축대 1 칭 해석 결과를 원주방향으로 확장하여 구 180°성 하였다.…”
unclassified
“…It is confirmed that the sealing capability of both types is fairly good, but the wrinkle type is better than the pot type in terms of the maximum stress. (8,9) 이러한 고 무의 특성을 잘 묘사하기 위해 고무의 인장시험 을 수행하였으며 그 결과로부터 과 같이 Table 1 함수 Ogden (9,10) 를 이용한 고무의 물성치를 구하 여 해석을 수행하였다. (7) 의 기능을 이용하여 단계의 축대 1 칭 해석 결과를 원주방향으로 확장하여 구 180°성 하였다.…”
unclassified